ENGLISH AS A NATIONAL LANGUAGE - Khaydarova Nigora; Axmadjonova Oydinoy (TADQIQOTLAR, 2025)
Abstract: This thesis explores the role of English as a national language and its impact on social, cultural, and educational development within multilingual societies. The study examines how English functions as a unifying linguistic tool, facilitating communication  among  diverse  ethnic  and  linguistic  groups.  It  also  analyzes  the advantages and challenges associated with adopting English as a national language, including  issues  of  identity,  language  preservation,  accessibility,  and  educational equity.  By  reviewing  global  examples  and  theoretical  perspectives,  the  research highlights how English contributes to national integration, global competitiveness, and modernization. The findings suggest that while English can promote social cohesion and international participation, careful policy planning is required to balance its use with the protection of native languages and cultural heritage.